Permeation-durability properties of metakaolin blended concrete containing rubber - Mohd Nasir, Noor Azline; Abu Bakar, Nabilah; Safiee, Nor Azizi; Abdul Aziz, Farah Nora Aznieta (Taylor & Francis, 2021)
Numerous works investigating the use of rubber waste as aggregate in concrete have been well documented. Most of the works covered the enhancement method in improving the mechanical properties of rubberized concrete. However, limited works on permeation-durability related characteristics of rubberized concrete have been reported. In this study, further understanding on metakaolin blended concrete containing 10% treated crumb rubber with respect to its permeation-durability behaviour is discovered. The effectiveness of rubberized concrete with the two-stage approach where sodium hydroxide solution treated crumb rubber combined with 15% metakaolin was evaluated on workability, compressive strength, permeation, and durability properties at a different level of superplasticizer (0.25%, 0.50%, 0.75%, and 1.0%). The permeation tests included absorption and permeability whereas rapid chloride permeability and carbonation tests were for durability assessment. The results showed that the reduction in permeation properties and better durability resistance were achieved at a superplasticizer level of 0.75%. Thus, it can be concluded that the good workability of concrete mixture able to discontinued pore connectivity and resulted in high permeation and durability resistance of metakaolin blended-rubberized concrete.